Faustovirus E12 Transcriptome Analysis Reveals Complex Splicing in Capsid Gene - Cherif Louazani, Amina; Baptiste, Emeline; Levasseur, Anthony; Colson, Philippe; La Scola, Bernard (Frontiers in Microbiology, 2018)
Faustoviruses are the first giant viruses of amoebae isolated on Vermamoeba vermiformis. They are distantly related to African swine fever virus, the causative agent of lethal hemorrhagic fever in domestic pigs. Structural studies have showed the presence of a double protein layer encapsidating the double-stranded DNA genome of Faustovirus E12, the prototype strain. The major capsid protein (MCP) forming the external layer has been shown to be 645-amino acid-long. Unexpectedly, its encoding sequence has been found to be scattered along a 17 kbp-large genomic region. Using RNA-seq, we studied expression of Faustovirus E12 genes at 9 time points over its entire replicative cycle. Paired-end 250 bp-long read sequencing on MiSeq instrument and double-round spliced alignment enabled the identification of 26 different splice-junctions. Reads corresponding to junctions represented 2% of mapped reads and mostly matched with the predicted MCP encoding sequences. Moreover, our study enabled describing a 1,939 bp-long transcript that corresponds to the MCP, delineating 13 exons. At least 2 types of introns coexist in the MCP gene: group I introns that can self-splice (n=5) and spliceosome-like introns with non-canonical splice sites (n=7). All splice-sites were non-canonical with 5 types of donor/acceptor splice-sites amongst which AA/TG was the most frequent association.